Model characteristics of anthropometric indicators of Juvenile category athletes in acrobatic rock'n'roll (preliminary preparatory stage) - Serhii Humeniuk; Nataliya Batieieva (Kharkiv State Academy of Physical Culture, 2017)
Purpose: to develop model characteristics of the anthropometric indicators of the Juvenile category in acrobatic rock'n'roll. Material & Methods: the following research methods were used: theoretical analysis and generalization of data from special scientific and methodological literature, methods of mathematical statistics. The study involved 20 sports couples (20 male partners and 20 female partners) of an acrobatic rock'n'roll category Juveniles aged 10-14 years. Results: obtained anthropometric indicators separately by male partners and female partners of sports pairs of acrobatic rock'n'roll. Based on the results obtained, model characteristics of anthropometric indicators of partners and partners of sports pairs of the Juvenile category of acrobatic rock'n'roll. Conclusion: it is established that the developed characteristics can be used to optimally select a male partner and female partner in pairs and also to improve the optimization of the training process in acrobatic rock'n'roll.